2011
DOI: 10.1017/s0029665111000103
|View full text |Cite
|
Sign up to set email alerts
|

Glucose sensing and signalling; regulation of intestinal glucose transport

Abstract: Epithelial cells lining the inner surface of the intestinal epithelium are in direct contact with a lumenal environment that varies dramatically with diet. It has long been suggested that the intestinal epithelium can sense the nutrient composition of lumenal contents. It is only recently that the nature of intestinal nutrient-sensing molecules and underlying mechanisms have been elucidated. There are a number of nutrient sensors expressed on the luminal membrane of endocrine cells that are activated by variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 81 publications
(137 reference statements)
1
92
1
Order By: Relevance
“…Our present findings implicating regulation of the colonic SCFA transporter MCT1 via nutrient sensing are of considerable interest because, despite the fact that colonic luminal SCFA levels vary significantly depending upon dietary composition, gut microbiota, and disease, a SCFA-sensing mechanism regulating colonic luminal SCFA absorption has not been described previously. In recent years, the importance of cell surface receptors in nutrient sensing has increasingly been recognized (21,29). For example, recent discovery of the expression of T1R sweet taste receptor families on the apical membranes of enterocytes suggested that activities of these receptors might underlie the mechanisms of enhanced glucose absorption via increased apical membrane insertion of Glut2 after a meal (21).…”
Section: Discussionmentioning
confidence: 99%
“…Our present findings implicating regulation of the colonic SCFA transporter MCT1 via nutrient sensing are of considerable interest because, despite the fact that colonic luminal SCFA levels vary significantly depending upon dietary composition, gut microbiota, and disease, a SCFA-sensing mechanism regulating colonic luminal SCFA absorption has not been described previously. In recent years, the importance of cell surface receptors in nutrient sensing has increasingly been recognized (21,29). For example, recent discovery of the expression of T1R sweet taste receptor families on the apical membranes of enterocytes suggested that activities of these receptors might underlie the mechanisms of enhanced glucose absorption via increased apical membrane insertion of Glut2 after a meal (21).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, there is an induction and functional activation of the glucose transporter SGLT1 [100]. Although the induction of SGLT1 is mediated through GLP-2, the GLP-2 receptor is on submucosal neurons, not on the epithelium, which implies that the increased glucose transport is a nerve-mediated effect [103]. GLP-2 excites submucosal neurons [104].…”
Section: Motor Neuron Influence On the Glucose Transportermentioning
confidence: 99%
“…It may be that postabsorptive glucose actions can reinforce flavor preferences when there is also preabsorptive nutrient stimulation as provided by the flavored chow used in the Tordoff and Friedman study. Currently, there is considerable interest in the role of intestinal T1R2ϩT1R3 sweet receptors in carbohydrate absorption and hormone release (19,55), but these gut receptors are not implicated in sugar-stimulated intake or flavor conditioning. In particular, the failure of fructose to stimulate drinking in experiment 1 and the relatively weak flavor conditioning effect of IG fructose observed in other studies (4,46,47) argues against the involvement of intestinal sweet receptors, because fructose is a potent sweet receptor ligand.…”
Section: Glucose Stimulated Intakementioning
confidence: 99%